Interventions to Reduce Problems Related to the Readability and Comprehensibility of Drug Packages and Labels: A Systematic Review. Issue 8 (7th December 2021) - Simas da Rocha, Bruno; Garcia Moraes, Cassia; Miyake Okumura, Lucas; da Cruz, Fernanda; Sirtori, Lisana; da Silva Pons, Emilia
Abstract : Supplemental digital content is available in the text. Abstract : Objective: The aim of the study was to evaluate the effectiveness of interventions designed to reduce problems with readability and comprehensibility in drug labels. Methods: A systematic review of observational and experimental studies was conducted using MEDLINE (via PubMed), Embase, and Scopus databases. Two independent reviewers selected articles and collected data about study design, interventions, and outcomes. Results: Of 1786 studies screened, 17 were included in this systematic review. The main findings were described according to the type of intervention in the drug package or label: color-coded labels (7 studies); changes in information layout (5 studies); changes in font size (3 studies); and interventions involving look-alike/sound-alike (LASA) drugs (3 studies). Color changes were important both for healthcare professionals to improve safety in hospital practice and for medication users to differentiate between the types of insulin. Layout changes were effective and included highlighting key information, such as medication name, dose, and instructions. Increased font size yielded good results in the recognition and identification of medications mainly for the population with impaired vision. This review was limited by the heterogeneity of interventions and populations studied, as well as the small number of high-quality studies, which prevented meta-analysis across any one intervention or outcome. Conclusions: All studies reported positive results for the proposed interventions. In the case of LASA drug names, the use of resources beyond Tall Man lettering (such as color and highlighting) reduced recognition errors, which may contribute to the development of new strategies to improve safety in the use of LASA drugs.